The impact of the COVID-19 pandemic exposure on the corporate cash policy of Vietnam-listed enterprises - Nguyen, An Binh; Do, Doan Trang; Le, Hoang Anh (The Economics and Finance Letters, 2024)
The purpose of this study was to assess the impact of the COVID-19 epidemic on the daily stock returns of 177 businesses listed on the Vietnam Stock Exchange during the period spanning from the second quarter of 2020 to the first quarter of 2023. Next, we proceed to evaluate the influence of COVID-19 exposure on the cash holding ratio of these enterprises. We used research methods for panel data, such as the fixed effects method and the system GMM method. Our findings demonstrate that the exposure of enterprises to the COVID-19 pandemic has a discernible and statistically significant adverse effect on their financial reserves. When conducting research on the transmission channel of COVID-19 exposure to cash holding policies, we found that this impact persists in firms through financial frictions. Based on the findings, we have put forth several policy implications for businesses to formulate cash management policies in anticipation of future pandemics of a similar nature.